Useful palms (Arecaceae) near Iquitos, Peruvian Amazon - Balslev, Henrik (2008)
This paper describes the uses of 64 species of palms in 28 villages in Departamento de Loreto, Peru. There, the palms are of great use as food (Bactris gasipaes, Mauritia flexuosa, Euterpe precatoria, Oenocarpus bataua), for fiber production (Astrocaryum chambira, Aphandra natalia), for construction of houses (Euterpe precatoria, Iriartea deltoidea,Socratea exorrhiza), thatching (many species of Attalea, Lepidocaryum tenue) and for many medicinal purposes (Euterpe precatoria, Oenocarpus bataua).